1990
DOI: 10.1007/bf00315573
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taprostene, a stable prostacyclin analogue, on haemodynamics, platelet function and arachidonate metabolism in healthy volunteers

Abstract: In order to assess the effect of taprostene on haemodynamics, platelet function and arachidonate metabolism in 4 healthy volunteers an intravenous infusion of 25 ng.kg-1.min-1 was given for 6 h. During the infusion period systolic blood pressure dropped from 130 to 111 mm Hg and diastolic blood pressure from 77 to 69 mm Hg. The heart rate rose from 77 to 84 beats/min. During the taprostene infusion the slope and height of the ADP and collagen induced platelet aggregation curves were significantly inhibited and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
0
8
2
Order By: Relevance
“…6 and 7). Treatment of HUVECs with the selective IP receptor agonist taprostene (Virgolini et al, 1990) at concentrations up to 6.3 μM increased migration (up to 193 ± 44% of control). Migration plateaued at~26 ± 4% of control at higher taprostene concentrations up to 25.1 μM (Fig.…”
Section: Effects Of Prostanoid Receptor Activation Followed By Desensmentioning
confidence: 95%
“…6 and 7). Treatment of HUVECs with the selective IP receptor agonist taprostene (Virgolini et al, 1990) at concentrations up to 6.3 μM increased migration (up to 193 ± 44% of control). Migration plateaued at~26 ± 4% of control at higher taprostene concentrations up to 25.1 μM (Fig.…”
Section: Effects Of Prostanoid Receptor Activation Followed By Desensmentioning
confidence: 95%
“…Vasodilator effects of taprostene were more pronounced in a study reported by Virgolini et al, (59) who infused the drug at a rate of 25 ng/kg/min for 6 h in four healthy volunteers. During infusion of taprostene, systolic blood pressure dropped from 130 f 12 to 1 1 1 k 5 mm Hg (p < 0.05), diastolic blood pressure decreased from 77 k 5 to 69 f 5 mm Hg (p < 0.05), and heart rate increased from 77 k 4 to 84 k 4 beats/min (p < 0.05).…”
Section: Clinical Studies Clinical Pharmacologymentioning
confidence: 87%
“…Such a rebound phenomenon did not occur during the infusion of taprostene in healthy volunteers where the sensitivity of platelets to the antiaggregatory effects of prostacyclin and prostaglandin E, was even enhanced whereas the response to prostaglandin D, and taprostene itself did not change. There was no satisfactory explanation for these differences in platelet sensitivity (93). Taprostene did not alter plasma or serum levels of thromboxane B,, platelet factor 4, or P-thromboglobulin in healthy volunteers, nor did it alter metabolism of exogenous radiolabeled arachidonic acid (93).…”
Section: Pharmacology In Volunteersmentioning
confidence: 93%
“…There was no satisfactory explanation for these differences in platelet sensitivity (93). Taprostene did not alter plasma or serum levels of thromboxane B,, platelet factor 4, or P-thromboglobulin in healthy volunteers, nor did it alter metabolism of exogenous radiolabeled arachidonic acid (93).…”
Section: Pharmacology In Volunteersmentioning
confidence: 93%